PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA PUSAT BIAYA - Mawarni, Zellinda; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to assess and to analyze how the use of responsibility accounting system can havea role in assessing the management performance. The object of the research is PT Starfood International. It is acompany which engages in the field of sardines production. The method of the research has been done by usingqualitative, The descriptive analysis technique is used by the researcher to describe the object as it is. The budgetpreparation process has been carried out by using bottom up budgeting, but the code of the center ofresponsibility has not been shown and the separation between controlable and uncontrolable cost has not beencarried out yet. The result of the discussion shows that by preparing the budget based on the responsibilityaccounting system therefore the manager of responsibility center is asked for the responsibility of controlablecost only. The performance assessment on raw materials and processed department has been carried outefficiently in which it can be known from the total difference between the budgeted cost and realized cost. It canbe concluded from the result of the analysis that by implementating the responsibility accounting system, theperformance assessment from the lowest to the highest rank can be carried out by the management more easierthan before. The responsibility accounting can be stated good if the budget is used and realized in accordancewith the determined standard.Keywords: Budget, Responsibility Accounting, Performance Assessment